WORKSHOP ON THE USE OF THE MOLVIEW APPLICATION IN CHEMISTRY EDUCATION AT SMA NEGERI 5 PALANGKA RAYA - Ruli Meiliawati; Suandi Sidauruk; Agtri Wulandari (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2023)
The purpose of implementing the Workshop on the Use of the MolView Application in Chemistry Education at SMA Negeri 5 Palangka Raya is to enable partner teachers (chemistry subject teachers) to facilitate students in visualizing molecular structures using the MolView application. The benefits of this activity include increasing insights and providing skills in developing teaching modules assisted by the MolView application in chemistry education. The stages of the workshop include 1) preparation stages, including field surveys, planning, administrative preparation, and providing support facilities; 2) training stages, including confirming attendance, Phase I training, Phase II training; 3) mentoring stages, including evaluation and participant support. The results of this activity can be reviewed based on participant satisfaction. This is evident from the questionnaire results filled out by the participants. In the workshop material aspect, the average score is 93.33%. The Team workshop aspect has an average score of 96.00%, the atmosphere aspect has an average score of 96.00%, and the media usage aspect has an average score of 93.78%. Furthermore, the overall satisfaction level of the workshop averages 94.78% with a